Adsorption studies of hexavalent chromium ions on the dead biomass of Cystoseira indica - Mahmood, Zahid; Zahra, Samreen; Ijaz, Izza (European Journal of Chemistry, 2022)
The biosorption of hexavalent chromium ions from aqueous solution was investigated using acid-modified dead biomass of the abundantly available brown marine alga Cystoseira indica from Karachi coastal area of Pakistan. The biosorbent was characterized by infrared spectroscopy and scanning electron microscopy. The optimum biosorption conditions, i.e., biosorbent dosage, contact time, initial metal ion concentration, pH, and temperature, were determined by carrying out batch-mode experiments. The sorption behavior was established by the Langmuir and Freundlich isotherms, which showed that although the uptake of metals was more feasible on a heterogeneous surface, homogeneous surface conditions seemed to exist at the same time. The thermodynamic parameters ∆G°, ∆H° and ∆S° calculated at different temperatures ranging from 298 to 318 K demonstrated that the biosorption was a spontaneous and exothermic process under the experimental conditions applied.